Intraparenchymal meningioma within the basal ganglia of a child: A case report. (3rd May 2016) - Reynolds, Matthew R.; Boland, Michael R.; Arias, Eric J.; Farrell, Michael; Javadpour, Mohsen; Caird, John
Abstract: Intraparenchymal meningiomas are rare. To date, no such lesion has been reported within the basal ganglia of a paediatric patient. Here, we describe the case of a 15-year-old-boy who presented with symptoms referable to a cystic, calcified, left basal ganglia intraparenchymal meningioma and discuss the surgical management of this lesion.